The Influence of Financial Literacy, Locus of Control, Gender, and Lifestyle on Financial Behavior Among the I-Generation in Jepara Regency - Hanun, Rias Untian; Widiastuti, Anna (Magister Manajemen of Universitas Islam Nahdlatul Ulama Jepara, 2025)
This research aims to exmine and analyze of Financial Literacy, Locus of Control, Gender, and Lifestyle on Financial Behavior among the I-Generation in Jepara Regency. Using a quantitative methodology, 96 respondents with independent incomes participated in purposive sampling to gather data. Data analysis employed Partial Least Square Structural Equation Modeling (PLS-SEM) using SmartPLS. The results show that locus of control and financial knowledge significantly and favorably affect financial behavior. In the meanwhile, lifestyle factors and gender have little bearing. This research provides empirical insights into the financial behavior of digital-native generations and offers implications for educational interventions and financial management practices.